Families as partners: Insights from kindergarten teachers on parental engagement in Saudi Arabia - Alhejii, Khawlah (Research Journal in Advanced Humanities, 2025)
Research validates the link between parental engagement in education and improvement of student outcomes. Although this link is agreed upon by educators, particularly in Saudi Arabia, the perceptions of teachers regarding parental engagement are very scarce. This study explores kindergarten teachers’ perspectives on parental engagement in Saudi Arabia, examining its impact on children’s academic, social, and emotional development, as well as barriers and strategies to enhance engagement. Based on survey data from 273 teachers, the findings highlight the critical role of parental involvement, with work-related commitments and socio-economic constraints identified as major barriers. Private schools reported more proactive engagement strategies than public schools, emphasizing structured communication and collaboration. The study underscores the need for targeted interventions, including resource allocation, teacher training, and community partnerships, to foster equitable and effective family-school collaboration in early childhood education.